A Proposal for Fishery Habitat Conservation Decision-Support Indicators. Issue 3 (3rd May 2016) - Lederhouse, Terra; Link, Jason S.
ABSTRACT: U.S. fisheries management is increasingly moving toward an ecosystem-based approach that considers multiple factors in setting targets to achieve fishery objectives. This approach is informed by ecological, social, and economic indicators of functioning and productive fishery ecosystems. However, a relatively limited number of habitat indicators, especially indicators that are related to fishery goals, have been developed and included in this approach. Fishery and habitat managers have had some success in establishing habitat metrics to guide fishery management decisions at smaller scales (e.g., sub-estuaries or river systems) but have not successfully scaled-up those types of metrics or applied them at broader regional or shelf-wide extents, where specific constraints on fish habitat are unknown or harder to quantify. This article explores indicators to guide marine fishery habitat conservation actions, with particular emphasis at the fish population and community levels. We propose a suite of possible habitat conservation decision-support indicators suitable for these broader scales and develop a performance measure to evaluate the efficacy of coastal and marine habitat conservation actions. These indicators can help fishery managers evaluate the effectiveness of habitat conservation actions to benefit fish populations.